The stock market: the entity and the definition - Харабара, Віолетта; Грешко, Роман Ігорович; Третякова, Олена Василівна (Economic strategies for the development of society, 2020)
At the present stage, Ukraine is in a state of transition to an independent sector of the economy, and this is due to the fact that the main indicator of the state of the country's economic sphere is the stock market, which depends entirely on any changes in the state. Infrastructure that has a strong position and creates appropriate conditions for the issuance and further circulation of securities is the main efficiency of the country's stock market. An active stock market, which is effectively regulated, is one of the most important factors in the development of the country's economy, as it is a powerful means of attracting capital to leading industries, both domestic and foreign investors. In Ukraine, the formation of the stock market actually began in 1991 with the adoption of the Law of Ukraine "On Securities and Stock Exchange". One of the main problems of Ukraine is the extremely low level of investment: both direct (strategic or real) and portfolio (financial), both internal and external. Direct investment comes to Ukraine very slowly, due to low production efficiency, difficulties with sales due to low solvency of the population and business, as well as high taxes. In this situation, it is the stock market that should become the source, the basis that will contribute to Ukraine's exit from the crisis and its further prosperity.
Keywords: securities; securities market; stock market; financial system of the country